2013
DOI: 10.1590/s0036-46652013000200001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasitism and Associated Symptomatology Among Hemodialysis Patients

Abstract: SUMMARYIntestinal parasites are an important cause of morbidity and mortality. Immunocompromised individuals may develop more severe forms of these infections. Taking into account the immunity impairment in patients suffering from chronic renal failure (CRF), we will determine the prevalence and associated symptoms of intestinal parasites in these patients. Controls without CRF were used for comparison. Stool samples were collected and processed for microscopic identification of parasites using the Formalin-et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
1
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 31 publications
6
22
1
11
Order By: Relevance
“…9 Diabetic patients have been reported to be immunocompromised. 1,[10][11][12] Intestinal parasites have gained increasing attention as important opportunistic pathogens responsible for clinically important infections in immunosuppressed patients.…”
Section: Introductionmentioning
confidence: 99%
“…9 Diabetic patients have been reported to be immunocompromised. 1,[10][11][12] Intestinal parasites have gained increasing attention as important opportunistic pathogens responsible for clinically important infections in immunosuppressed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the some countries where education excel and adequate sanitation conditions, some of these parasites had an important role in causing diseases in specific groups such as immune-compromised individuals (Fantry, 2002), organ diseases such as diabetes (Nazligul et al, 2001), among renal failure patients (Gil et al, 2013).…”
mentioning
confidence: 99%
“…It is worth discussing this as it probably represents a further risk factor for transmission especially if this was shown to be in young children from which transmission is likely to occur. Although prevalence of asymptomatic careers in this study was reported as high as 75%, this range may be variable by species of Cryptosporidium , the general health condition of human host for example being immunocompromised such as HIV positive and kidney transplant patients, the prevalence of positive calves and animal and previous outbreaks in that geographical region [4649]. …”
Section: Discussionmentioning
confidence: 96%